Prospective Evaluation of the Efficacy of Isolated Balloon Eustachian Tuboplasty: Short- and Medium-term Follow-up Results Based on Tubomanometry, ETDQ-7, Tympanometry, and Valsalva Maneuver - Azevedo, Cátia; Moreira, Filipa; Lima, António Fontes; Mar, Fernando Milhazes; Vilarinho, Sérgio; Dias, Luís (International Archives of Otorhinolaryngology, 2023)
Introduction Balloon eustachian tuboplasty (BET) allows the treatment of the main etiology of eustachian tube disfunction (ETD).Objective To evaluate the efficacy of isolated BET, through objective and subjective results, in the short and medium term, in patients with chronic obstructive ETD.Methods Adult patients diagnosed with chronic obstructive ETD who underwent BET between January 2018 and December 2020 were enrolled in the study. We performed a prospective observational study of BET efficacy, by comparing subjective data, based on the Eustachian Tube Dysfunction Questionnaire-7 (ETDQ-7), and objective data, obtained by tympanometry, objective Valsalva maneuver and tubomanometry, prior to BET with these outcome tools on postprocedure follow-up.Results In total, 30 BETs were performed and analyzed. There were no complications with the procedure. Analysis of BET efficacy was performed in the short-term (average of 7.5 weeks) and in the medium-term (average of 8 months). There was a significant reduction (p < 0.0001) in the total ETDQ-7 score from baseline to both follow-up periods. A normalization of the ETDQ-7 score was observed in 60 and 83.3% of the performed procedures, in the short- and medium-term, respectively. In tubomanometry, we verified a significant improvement (p < 0.0001) at all pressures, with a normalization of tubomanometry values in 53.3% and 43.3% of cases in the short- and medium-term, respectively. Tympanogram normalization occurred in 71.4% of patients with abnormal preoperative assessments.Conclusion As an isolated procedure, BET results in significant improvements in symptomatology and objective metric results. This, associated with its safety profile, currently makes BET the most indicated therapeutic option in refractory obstructive ETD.
Keywords: eustachian tube; acoustic impedance tests; eustachian tube surgery